Application of a filter press to a sludge dewatering process in the Bangkhen water treatment plant - Sopin Paethong; Takizawa, S.; Visvanathan, C.; Samorn Muttamara; Metropolitan Waterworks Authority (MWA) (Bangkok : Asian Institute of Technology, 1998)
This research study emphasized mechanical dewatering characteristics and attempted to investigate the use of filter press in Bangken Water Treatment Plant because it was anticipated that in the not-too-distant future the filter press would be considered. Although previous systems are generally not economically feasible for most treatment plants, improvements in technology and adjustments in materials and system costs may make them more attractive in the future. The specific resistance of the conditioned sludge and CST are determined. They are found that the addition of optimum dosage of chemicals improve the filterability of sludge to a high degree, in which the specific resistance of the sludge is decrease from an average of 6.53E+ 11 m/kg to7.48E+10 m/kg. The figure revealed the optimum dosage of Ze Tag 63, anionic polymer to be 0.08% DS sludge. A comparison between combination of chemical conditioners to apply in filter pressing operation indicate that by using anionic polymer with lime in place of cationic would fall in CST value of 10.7 s, however, the cost of lime and anionic polymer might be higher than that of cationic polymer for the same degree of conditioning.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1998
Keywords: Water -- Purification -- Filtration; Sewage sludge -- Drying